Words in the wilderness : critical literacy in the borderlands - Brown, Stephen Gilbert, 1949- (Albany, N.Y. : State University of New York Press, 2000)
Reflecting and building upon his time teaching on an Athabascan Indian reservation in Alaska, Brown (writing, U. of Tampa) attempts to incorporate his experience and the theories of Freire and other critical pedagogists into a work which recommends a resistance pedagogy for colonized and oppressed peoples. He relates his own transformation from a unwitting tool of the colonizer to someone who learned from his students what works in engaging "border" students education, throughout relating the material to current theoretical radical pedagogy.
Foreword / Gary A. Olson -- Introduction: Of Words in the Wilderness -- How I Came to Be a Bush Teacher -- Calibans of the Contact Zone: Resistance and Marginality in the Borderlands -- The Bush Teacher as Cultural Imperialist -- Beyond the Contact Zone: Theorizing the Dialogic Classroom -- Adventures in Cultural Tourism: Foxfire and the Fetishization of the Authentic -- Decomposing the Canon: Alter/Native Narratives from the Borderlands -- Teaching the Cultural Conflicts: Toward a Literacy of Resistance.
Includes bibliographical references (pages 217-224) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Brown, Stephen Gilbert, -- 1949-; Brown, Stephen Gilbert, -- 1949-; Brown, Stephen Gilbert, -- 1949-; Athapascan Indians -- Education -- Alaska; Critical pedagogy; Literacy; Teachers -- Alaska -- Biography; Teachers -- Alaska -- Biography; Educational Status; Athapascan -- Éducation -- Alaska; Pédagogie critique; Alphabétisation.; Enseignants -- Alaska -- Biographies; Enseignants -- Alaska -- Biographies; literacy; BIOGRAPHY & AUTOBIOGRAPHY -- Educators; EDUCATION -- Students & Student Life; Athapascan Indians -- Education; Critical pedagogy; Literacy; Teachers; Alaska; Biographies